Rancang Bangun Alat Otomatis Pakan Ayam Menggunakan Motor Servo Berbasis Arduino Uno - Bayu Kusumo; Bayu Fikri Triyanto; Teten Dian Hakim (Teknik Elektro Universtias Krisnadwipayana, 2025)
This research focuses on designing an automatic chicken feeding device based on Arduino Uno which is designed to increase efficiency and regularity in feeding. This system uses an Arduino Uno as a controller, a servo motor for the feeding mechanism, an infrared sensor to detect the presence of feed, and an I2C LCD to display status and monitoring data. When the sensor detects the feed bin is empty, the servo motor is activated to open, fill the feed, and close the feed bin again. Tests show that this system is able to manage feeding 500 grams of feed to the silo well. The average feed spilled when the servo motor is open is 42.75 grams at a 30° angle, 84.75 grams at a 45° angle, 100 grams at a 65° angle, and 177.75 grams at a 90° angle. This system reduces human involvement and ensures feed is provided evenly and regularly. The infrared sensor has high accuracy, and the servo motor functions well in the feeding mechanism. In addition, feed status can be monitored in real-time via LCD and Serial Monitor. In conclusion, this tool is effective for increasing the productivity and efficiency of chicken farming. Further development is suggested for IoT integration and adaptation for different types of poultry as well as environmental conditions.